Does fintech innovation and green transformational leadership improve green innovation and corporate environmental performance? A hybrid SEM-ANN approach - Huawei Tian; Abu Bakkar Siddik; Thillai Raja Pertheban; Md Nafizur Rahman (Journal of Innovation & Knowledge (JIK), 2023)
This study uses the ecological modernization theory (EMT) and ability-motivation-opportunity (AMO) perspectives to determine the roles of fintech innovation and green transformational leadership (GTL) in enhancing corporate environmental performance (ENP). Additionally, we explore the mediating role of firms' green innovation among these associations. We analyze our conceptual model using survey data from 286 Bangladeshi manufacturing small and medium-sized enterprises (SME) managers. This study employs a two-staged hybrid structural equation modeling-artificial neural network (SEM-ANN) technique to assess the hypotheses. Our empirical findings suggest that fintech adoption has a positive linkage with SMEs' green innovation and ENP. We also observe that GTL substantially affects organizations' green innovation and ENP. Green innovation was found to enhance ENP in manufacturing SMEs. Our findings reveal that green innovation mediates the linkages between fintech adoption and ENP and between GTL and ENP. These novel findings contribute to fintech, GTL, and environmental literature and expand the scope of the EMT and AMO theory. Our research provides SME managers and policymakers with a constructive model for implementing fintech and managers' GTL to enhance green innovation and performance. The results may assist manufacturing firms' managers in integrating technological advancements and human capital to alleviate adverse environmental concerns.
Keywords: 650; Environmental performance; Fintech innovation; Green innovation; Green transformational leadership; SEM-ANN approach